Dissatisfied with life, but having a good day: time-use and well-being of the unemployed - Andreas Knabe; Steffen Rätzel; Ronnie Schöb; Joachim Weimann (Center for Economic Studies and ifo Institute (CESifo), 2009)
We apply the Day Reconstruction Method to compare unemployed and employed people with respect to their subjective assessment of emotional affects, differences in the composition and duration of activities during the course of a day, and their self-reported life satisfaction. Employed persons are more satisfied with their life than the unemployed and report more positive feelings when engaged in similar activities. Weighting these activities with their duration shows, however, that average experienced utility does not differ between the two groups. Although the unemployed feel sadder when engaged in similar activities, they can compensate this by using the time the employed are at work in more enjoyable ways. Our finding that unemployment affects life satisfaction and experienced utility differently may be explained by the fact that people do not adjust their aspirations when becoming unemployed but face hedonic adaptation to changing life circumstances, triggered by the opportunity to use the time in a way that yields higher levels of satisfaction than working.
Keywords: I31; J60; J22; 330; Unemployment; happiness; life satisfaction; Day Reconstruction Method; experienced utility; Arbeitslosigkeit; Zeitbudgetforschung; Lebenszufriedenheit; Zeitpräferenz; Deutschland